Guidelines for Corticosteroid use in Treatment of DMD - Vamshi K. Rao (Pediatric Neurology Briefs, 2016)
The guideline development subcommittee of the American Academy of Neurology has provided an update to the 2005 treatment guidelines for use of corticosteroids (CS) in Duchenne muscular dystrophy (DMD).